2023
DOI: 10.1002/advs.202206195
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Tumor‐Mimicking In Vitro Drug Release Model of Locoregional Chemoembolization Using Deep Learning‐Based Quantitative Analyses

Abstract: Primary liver cancer, with the predominant form as hepatocellular carcinoma (HCC), remains a worldwide health problem due to its aggressive and lethal nature. Transarterial chemoembolization, the first-line treatment option of unresectable HCC that employs drug-loaded embolic agents to occlude tumor-feeding arteries and concomitantly delivers chemotherapeutic drugs into the tumor, is still under fierce debate in terms of the treatment parameters. The models that can produce in-depth knowledge of the overall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The ex vivo drug release of DOX and ACF in TE and PE was accessed in decellularized liver model (DLM) as a previous study reported . Briefly, fresh livers were harvested from healthy male Sprague–Dawley rats (∼300 g) after euthanasia with carbon dioxide and stored at −80 °C for more than 24 h before decellularization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ex vivo drug release of DOX and ACF in TE and PE was accessed in decellularized liver model (DLM) as a previous study reported . Briefly, fresh livers were harvested from healthy male Sprague–Dawley rats (∼300 g) after euthanasia with carbon dioxide and stored at −80 °C for more than 24 h before decellularization.…”
Section: Methodsmentioning
confidence: 99%
“…The ex vivo drug release of DOX and ACF in TE and PE was accessed in decellularized liver model (DLM) as a previous study reported. 27 Briefly, fresh livers were harvested from healthy male Sprague−Dawley rats (∼300 g) after euthanasia with carbon dioxide and stored at −80 °C for more than 24 h before decellularization. To prepare DLM, the liver was first thawed to room temperature and then perfused with deionized water for 0.5 h, 4% Triton X-100 containing 0.02% EGTA for 1 h, and 0.5% SDS solution for 5 h through the portal vein to remove cellular components.…”
Section: Ex Vivo Drug Release Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed a simple model of decellularized liver tissue for basic laboratory research. Decellularization involves employing a combination of physical and chemical treatments to effectively eliminate cellular contents from tissue or organs while preserving extracellular matrix (ECM) components and functional proteins [25][26][27][28][29]. The resulting decellularized liver yields a translucent bioscaffold comprising an acellular natural matrix, maintaining both vascular system integrity and mechanical strength [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The ion-exchange microspheres currently applied in DEB-TACE, which possess high affinity between the fixed anionic groups of the beads with the soluble positively charged chemotherapeutic drugs, present high drug loading capacity that strongly depends on the anionic densities inside the microsphere bulk. , However, for degradable embolic agents, the chemical conjugation of anionic functional groups of extremely high densities can be challenging if considering the restricted selections of biodegradable materials for translation purpose . For instance, gelatin sponge particles, one of the most widely used materials in clinical interventions for tumor vascular embolization, represent an ideal biodegradable material with well-proven excellent biocompatibility and appropriate in vivo degradation rates varying from one to several months. Nevertheless, the gelatin-based particles are clinically employed as blank embolic agents without drug loading but present inferior drug-carrying properties in previous efforts. To circumvent this problem, we propose to graft nanosized highly charged low-molecular-weight anionic oligomers, instead of scattered anionic groups, into the main chain of degradable polymer, which can not only efficiently increase the overall anion density but also take advantage of the associated counterion condensation effect , to greatly improve the drug loading performance for the demanding requirements of embolic drug carriers.…”
Section: Introductionmentioning
confidence: 99%